A model for predicting high BMI of people living with HIV after receiving antiretroviral therapy. (June 2022) - Qian, Zhe; Wu, Houji; Wu, Yihua; Liao, Wei; Yu, Tao; Xu, Xuwen; Peng, Jie; Cai, Shaohang
Objective: The objective of this study was to evaluate the characteristics of high body mass index (BMI) and normal weight people living with HIV after antiretroviral therapy (ART) and establish a model. Methods: A total of 290 people living with HIV after 1 year of ART treatment were enrolled and divided into two groups based on whether their BMI index was <24 or ⩾24 at week 48. The demographic, clinical data were collected and analyzed. Multivariable logistic regression analysis was performed. A model was established and use to predict the occurrence of certain diseases. Results: A total of 290 people living with HIV were included in this study; 200 had a normal BMI (BMI < 24) and 90 were high BMI (BMI ⩾ 24) after 1-year ART. Their baseline characteristics were significantly different in relation to age ( p  = 0.007), sex distribution ( p  = 0.040), ART regimen ( p  = 0.040), alanine aminotransferase levels ( p  < 0.001), and three major serum lipid levels: triglycerides ( p  < 0.001), cholesterol ( p  = 0.011), and low-density lipoprotein ( p  = 0.005). A multivariate logistic regression analysis resulted in the development of a model for the diagnosis of high BMI and hyperlipidemia. The model score is an independent risk factor for hyperlipidemia (odds ratio = 2.674, p  = 0.001) and high BMI ( p  < 0.001). The model score is significantly correlated with the controlled attenuation parameter (CAP) value ( r  = 0.230, p  < 0.001) and can be used to divide the severity of liver steatosis based on CAP value. Conclusions: This study demonstrated a easy-to-use model to detect high BMI, hyperlipidemia, and liver steatosis in people living with HIV without risk factors for BMI changing at baseline after 1 year of ART treatment.